Islamic banking and economic growth: the Indonesian experience - Abduh, Muhamad; Omar, Mohd. Azmi (Emerald Group Publishing, 2012)
Purpose – The purpose of this paper is to examine the short-run and the long-run relationships between Islamic banking development and economic growth in the case of Indonesia.